Educação e migração: sentidos da escola para as famílias haitianas em Goiás - Ludovico, Daniela Collela Zuniga (2021)
This dissertation has as main objective to understand the meanings related to school by haitians families as a strategy for social and cultural integration and insertion. They unfold as specific objectives: understanding contemporary migratory movements in Brazil and in the world, identifying their causes and consequences; understand the relationship between migration and education in contemporaneity and its consequences; identify the meanings that Haitian migrants attribute to school. With the reconfiguration of global migratory flows, societies have increasingly faced issues related to diversity and the integration of migrants into the social life of the places of destination. Thinking about migrant human rights from the perspective of human rights is the challenge that States face. The right to education, understood as a human right, is guaranteed by international and national documents to all people, including those in a migration situation. Thus, thinking about the relationship between migration and education is a condition for identifying the meanings of school for haitians families as migrants. As a methodological procedure, questionnaires were carried out according to ten Haitian families. The declarations and questionnaires made it possible to identify 4 meanings considered to the school, which are, formative, practical economic, social and social protective. It is concluded that, much more than social integration, haitians families attribute to the school the possibility of social transformation, through training, which includes higher education